Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper analyzes Belgium's fiscal stance using a structural stochastic model. This note uses a theoretical model that explicitly accounts for the trade-offs between the short-term cost of fiscal tightening and the long-term gains associated with higher fiscal buffers. This paper shows that once the current crisis is over, rebuilding fiscal buffers is essential to helping Belgium confront the next shock from a stronger fiscal position. Overall, this illustrates a major motivation for a credible medium-term fiscal consolidation strategy. When a government reduces debt, it increases its capacity to react to shocks later. This entails a short-term cost that is, in the case of Belgium, worth the effort as this capacity to smooth future shocks increases future welfare. In addition, a large capacity to react with fiscal policy reduces the risk of long-lasting effects of a large crisis. Historical data show that in the past, the Belgium government's reaction to the cycle was limited to a single event. By contrast, if Belgium could firmly anchor public debt on a downward path, future governments would be able to offset downturns while keeping debt sustainability concerns under control.